HKT1;5 Transporter Gene Expression and Association of Amino Acid Substitutions With Salt Tolerance Across Rice Genotypes - Shohan, Mohammad Umer Sharif; Sinha, Souvik; Nabila, Fahmida Habib; Dastidar, Shubhra Ghosh; Seraj, Zeba I. (Frontiers in Plant Science, 2019)
Plants need to maintain a low Na+/K+ ratio for their survival and growth when there is high sodium concentration in soil. Under these circumstances, the High Affinity K+ Transporter (HKT) and its homologs are known to perform a critical role with HKT1;5 as a major player in maintaining Na+ concentration. Preferential expression of HKT1;5 in roots compared to shoots was observed in rice and rice-like genotypes from real time PCR, microarray and RNAseq experiments and data. Its expression trend was generally higher under increasing salt stress in sensitive IR29, tolerant Pokkali, both glycophytes; as well as the distant wild rice halophyte, P. coarctata, indicative of its importance during salt stress. These results were supported by a low Na+/K+ ratio in Pokkali, but a much lower one in P. coarctata. HKT1;5 has functional variability among salt sensitive and tolerant varieties and multiple sequence alignment of sequences of HKT1;5 from Oryza species and P. coarctata showed 4 major amino acid substitutions (140 P/A/T/I, 184 H/R, D332H, V395L), with similarity amongst the tolerant genotypes and the halophyte but in variance with sensitive ones. The best predicted 3D structure of HKT1;5 was generated using Ktrab potassium transporter as template. Among the 4 substitutions, conserved presence of Aspartate (332) and Valine (395) in opposite faces of the membrane along the Na+/K+ channel was observed only for the tolerant and halophytic genotypes. A model based on above, as well as molecular dynamics simulation study showed that Valine is unable to intrigue strong hydrophobic network with its surroundings in comparison to Leucine due to reduced side chain length. The resultant alteration in pore rigidity increases the likelihood of Na+ transport from xylem sap to parenchyma and further to soil. The model also proposes that the presence of Aspartate at the 332 position possibly leads to frequent polar interactions with the extracellular loop polar residues which may shift the loop away from the opening of the constriction at the pore and therefore permit easy efflux of the Na+. These two substitutions of the HKT1;5 transporter probably helps tolerant varieties maintain better Na+/K+ ratio for survival under salt stress